Seagrass biomass and shoot density in Changuu Island (Zanzibar Archipelago, Tanzania) during macrofauna exlcusion and nutrient enrichment experiment - Agustín Moreira-Saporiti; Mirta Teichberg; Aoife O extquotesingleSullivan (PANGAEA, 2026)
Seagrass biomass and shoot density was taken during a nutrient enrichment and macrofauna exclusion experiment. A total of 24 plots were set up parallel to the shore, with presence of the three seagrass species (Syringodium isoetifolium, Thalassodendron ciliatum and Thalassia hemprichii) in each plot. The experiment was the factorial combination of two treatments: macrofauna exclusion using cages (three levels: open, closed and uncaged) and nutrient enrichment using garden NPK fertilizer (two levels: ambient and enriched). Each treatment combination was replicated four times. Exclusion treatment simulates the consequences for the food web of losing a top predators and macrograzers. Nutrient enrichment was simulated by issuing nitrogen-phosphorus-potassium (NPK) [15:9:20] fertilizer pellets. NPK fertilizer fast release pellets were packed into cotton tubes and then into a perforated plastic tubes to simulate slow release of nutrients. The tubes were buried half-way into the sediment to ensure enrichment of both the water column and the sediment. Data was collected between July 19th and September 20th of 2017 in four sampling times. Day 0 (19.07.2017), Day 20 (09.08.2017), Day 38 (31.08.2017) and Day 63 (19.09.2017). Data collection and experiment took place in Changuu Island (Zanzibar Archipelago, Tanzania; 0611 extquotesingleS, 3916 extquotesingleE). Changuu Island is located 3 km from Stone Town, Zanzibar extquotesingles busiest town. Changuu remains relatively unaffected by nutrient runoff pollution. The study area is characterised by a fringing reef around a multi-specific seagrass ecosystem. The substrate is primarily carbonate sediment. Average water depth is approximately 30 cm at Spring Low and 5 m at Spring high tide with an average depth of 2 m. Seagrass biomass and shoot density was collected to study the effect of nutrient enrichment and macrofauna exclusion on the seagrass community and per species present. To determine the change in seagrass abundance in the treatments, biomass sampling was done using a core with a diameter of 15 cm and a shovel. Each treatment plot was divided in four "subplots", and at each sampling time a biomass core was taken from one of the four subplots inside the plot. The cores were transferred to a mesh bag and shaken vigorously to eliminate the sediment. In the laboratory, all collected seagrass shoots were cleaned with fresh water and separated according to the species. Dry weight of each seagrass species was determined after drying in an oven at 60C for 48 hours until constant dry weight. The final weight was divided by the core area (0.07 m2) to obtain g DW m-2. Within the biomass core, the number of seagrass shoots per species were also counted and divided by the core area to obtain shoot density (number of shoots m-2).